Politik Identitas Islam : Studi Perilaku Pemilih Muslim di Kecamatan Paciran Kabupaten Lamongan pada Pemilu 2019 - Mukayat, Al-amin (Universitas Muhammadiyah Surabaya, 2021)
The 2019 Presidential Election in Indonesia was considered highly tense and had the potential to trigger conflicts among fellow countrymen. The argumentation involves two crucial aspects. Firstly, with only two pairs of candidates, namely Jokowi-Ma'ruf Amin and Prabowo-Sandiaga Uno, it led to a division among Indonesian voters due to the lack of alternative choices. Secondly, religious identity politics played a strong role in the 2019 Presidential Election campaign, deemed capable of threatening national unity. This paper analyzes the practice of identity politics in the 2019 Presidential Election using identity theory. The research highlights the social history of Islam and the politics of identity developed by Islamic political parties in the Paciran Sub-district, Lamongan. Additionally, the study also explores the political identity contestation within Islamic political parties in competing for Muslim voters in the sub-district. The results indicate that a long history of identity struggles has occurred in Paciran Village, and this ongoing contest is produced by community agents and structures to win candidates through arguments of shared identity, facilitating voter mobilization on behalf of the same identity. Keywords: Identity Politics, History, and Contestation